Synthesis and characterization of thermally stable red light-emitting Eu3+ activated Li7La3Zr2O12 phosphors for solid-state lighting applications - K. Ganesh Kumar; P. Balaji Bhargav; Mohamed Abbas (Journal of Information Display)
To enhance the photoluminescence property of Li7La3Zr2O12 (LLZO), Eu was doped using a solid-state synthesis technique. X-ray diffraction and Raman spectroscopy analysis were used to examine the crystal structure of the synthesized phosphors. The optical band gap values of pristine and Eu3+ doped LLZO phosphor investigated using ultraviolet-visible (UV-Vis) spectroscopy were measured to be 2.74 and 2.97 eV, respectively. The wavelengths of pure and doped LLZO samples were measured and fitted by the Commission Internationale de l’Eclairage (CIE) chromatic coordinate graph. These samples were found to emit blue emission at 354 nm (pure LLZO) and red emission at 464 nm (doped phosphor), which correspond to the 5D0 to 7Fj (j = 0, 1, 2, and 3) transition. The purity of the color and correlated color temperature with respect to the 0.9 M.W% Eu3+ doped (activated) LLZO sample were estimated to be 80% and 1719K, respectively. The indication of its maximum emissive capability at this rate was found suitable for aesthetic lighting applications.